Surf therapy for improving child and adolescent mental health: A pilot randomised control trial. (March 2023) - Olive, Lisa; Dober, Madeleine; Mazza, Catherine; Turner, Alyna; Mohebbi, Mohammadreza; Berk, Michael; Telford, Rohan
Abstract: The aim of this pilot randomised control trial (RCT) was to test, 1) feasibility and acceptability of a surf therapy program to improve symptoms of mental ill-health among children and adolescents, and 2) the design and procedures of an evaluative study. This pilot RCT compared a 6-week mentor-supported surf therapy program with a wait list control group, in Australian children and adolescents aged 8–18yrs (M age = 11.28, SD = 2.34; 15 females), who were help seeking for issues relating to their mental health. Exclusion criteria included if an individual was actively suicidal or experiencing a psychotic episode or being unavailable for program dates. The primary outcome was the feasibility and acceptability of the intervention and study design assessed via 11 pre-defined criteria. A secondary outcome was to investigate the effectiveness signal of the intervention on child indicators of depression and anxiety, assessed via the Revised Children's Anxiety and Depression Scale-Short Form and the Strengths and Difficulties Questionnaire. Random allocation was computer generated and while it was not possible to blind participants, researchers collecting assessments were blinded to group allocation. Thirty-six youth were randomised (intervention = 18; wait list controls = 18), representing an 84% participation rate among eligible youth. Of the 11 a priori feasibility and acceptability criteria, 4 of 5 relating to the intervention, and 4 of 6 addressing the study design were fully met, with the unmet factors guiding program revision. At the completion of the intervention, children and adolescents receiving the intervention reported reductions in symptoms of depression (ES = 0.57), anxiety (ES = 0.43), emotional problems, (ES = 0.79), peer problems (ES = 0.56), hyperactivity/inattention (ES = 0.28), and overall difficulties (ES = 0.64). These reductions were not sustained 6-weeks after completion of the intervention. Surf therapy is an acceptable and feasible intervention for addressing symptoms of mental ill-health among children and adolescents. Preliminary evidence suggests that surf therapy improves symptoms of mental ill-health in the short-term but that these improvements were not sustained after the intervention is ceased. Highlights: Children receiving surf therapy had greater reductions in symptoms of mental ill-health than those in the control group. Mental ill-health symptom reduction was not sustained 6-weeks post program. Surf therapy is a feasible and acceptable intervention for managing child and adolescent mental ill-health. A definitive RCT study design is an appropriate next step to assess the mental health effects of surf therapy.